Compelling Pregnancy at Death’s Door: Heeding Harms to Women - Taylor, Katherine A. (Columbia Journal of Gender and Law, 1997)
In December 1995, a nurse in a Rochester nursing home noticed that a 29 year old female patient had a swollen belly. It was later discovered that the woman was pregnant, though she had been in a coma for ten years. While her rapist has since been convicted, it was not only the rape itself that caught the nation’s attention, but the decision by the comatose woman’s parents to continue her pregnancy. The following March, a baby boy was born two months premature, and the woman’s mother was awarded guardianship. Ethicists and others lined up on both sides of the controversy, some supporting the parents’ decision, and others decrying the “almost grotesque” use of the woman’s body as a fetal incubator. One ethicist observed that, “The case is beyond our imagination. Something like that would never even cross our minds. And, here it is.” But in fact, something “like that” has crossed the minds of legislators in most states. Thirty-six states mandate, through their advance directive statutes, that an incompetent pregnant woman be kept alive under certain circumstances, despite her earlier wishes expressed in a living will, or, in many states, the wishes of her designated healthcare decisionmaker.